Uncommon abdominal pain: A case report on spontaneous superior mesenteric artery dissection - Anuroop, Jakkani; Gandham, Sohini; Meraj, M D; Moorthy, N L N (Indian Journal of Case Reports, 2024)
Spontaneous isolated superior mesenteric artery dissection (SISMAD) is a rare cause of abdominal pain, with symptoms ranging from incidental discovery to severe complications, such as acute bowel ischemia or a potentially fatal rupture of a superior mesenteric artery aneurysm. First reported in 1946, SISMAD is an uncommon vascular condition, accounting for